Borderline resectable pancreatic cancer - Hackert, Thilo; Ulrich, Alexis; Büchler, Markus W. (Cancer letters, 2016)
Surgery followed by adjuvant chemotherapy remains the only treatment option for pancreatic ductal adenocarcinoma (PDAC) with the chance of long-term survival. If a radical tumor resection is possible, 5-year survival rates of 20-25% can be achieved. Pancreatic surgery has significantly changed during the past years and resection approaches have been extended beyond standard procedures, including vascular and multivisceral resections. Consequently, borderline resectable pancreatic ductal adenocarcinoma (BR-PDAC), which has recently been defined by the International Study Group for Pancreatic Surgery (ISGPS), has become a controversial issue with regard to its management in terms of upfront resection vs. neoadjuvant treatment and sequential resection. Preoperative diagnostic accuracy to define resectability of PDAC is a keypoint in this context as well as the surgical and interdisciplinary expertise to perform advanced pancreatic surgery and manage complications. The present mini-review summarizes the current state of definition, management and outcome of BR-PDAC. Furthermore, the topic of ongoing and future studies on neoadjuvant treatment which is closely related to borderline resectability in PDAC is discussed.